Tāhā Jābir al-ʻalwānī’s viewpoint on apostasy : an analytical study from Bangladesh perspective - Hossen, Belayet; Abdul Bari Awang (Pusat Penyelidikan Syariah, Fakulti Pengajian Islam, Universiti Kebangsaan Malaysia, 2021)
This research aims to illustrate the notion of apostasy in the viewpoint of late Tāhā Jābir Al-ʻalwānī in the Bangladesh perspective where apostates are usually killed by known or unknown Islamic hardliner groups without any legal authorization. This research finds the notion of apostasy is still now crucial and debate-full among the scholars of early and latter generation of Islam. Contemporary scholars also have been divided over the issue. Tāhā Jābir Alʻalwānīis one of them who critically conducted a research regarding the issue where he showed the irrationality of apostasy’s punishment. However,‘Alwānī said putting an apostate to death is opposite of the Qurʼānic viewpoint, Prophetic tradition and his rightly guided Caliphs. To him the issue lacks consensus among the Prophet’s companions and scholars of later generation. He dismissed the penalty of apostasy showing verses of the Qurʼān describing no punishment. Through explaining the historical evidences and other sources of Islam he opined that the execution for apostasy happened at different periods of Islam was mostly by politically motivated where several Muslim scholars have been accused of apostasy when they did not consent the actions of respective rulers. The researcher has found a pragmatic relevance to further study and analyze the apostasy issue of ʻAlwānī in the Bangladesh context where the mainstream ʻulamāʼ forbid such act. The research has followed the qualitative methodology, extracted the ʻAlwānī’s views scanning his written book on the issue, video lectures and other many more verified sources from Bangladesh research circle.